Appointment of Dr. Manuel Lopez as dean of the College of Computer Studies - De La Salle University, Manila (Animo Repository, 1993)
The Office of the President announced the appointment of Dr. Manuel Lopez as Dean of the College of Computer Studies effective May 15, 1993. He replaces Mitch Andaya who resumes his teaching assignments.